PUBLIC KNOWLEDGE AND ATTITUDE TOWARDS COVID-19 VACCINATION IN JOMBLANG, SONOREJO VILLAGE, SUKOHARJO REGENCY - Bangkit Ary Pratama; Siwi Hastuti; W Wahyuni (P3M Universitas 'Aisyiyah Surakarta, 2022)
Vaccination was the most effective strategy to protect populations from Covid-19, as SARS-CoV-2 was a highly contagious virus and affects populations globally. Many obstacles were found in the implementation of vaccination, such as the loss of confidence in the effect of vaccination causing low vaccination coverage. This study aimed to analyze the relationship between community knowledge and attitudes towards Covid-19 vaccination in Jomblang, Sonorejo Village, Sukoharjo Regency. This research was a quantitative research with the type of correlational research. The population in this study were all residents of Jomblang, Sonorejo Village, Sukoharjo Regency with a sample of 60 people. The sampling technique used was purposive sampling. The data collection technique used a structured questionnaire. The primary data obtained were then analyzed by univariate and bivariate (Chi square). The results of the statistical test showed that there was a relationship between knowledge about Covid-19 vaccination and vaccination with Â p-value (<0.001)<0.05 and there was a relationship between attitudes towards Covid-19 vaccination and Covid-19 vaccination with Â p-value (0.022)< 0.05. The conclusion of this study showed there was a significant relationship between knowledge about Covid-19 vaccination and people's attitudes towards Covid-19 vaccination and Covid-19 vaccination in Jomblang, Sonorejo Village, Sukoharjo Regency.